2018
DOI: 10.1186/s12882-018-1142-8
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jiroveci pneumonia in kidney and simultaneous pancreas kidney transplant recipients in the present era of routine post-transplant prophylaxis: risk factors and outcomes

Abstract: BackgroundThe goal of this study was to identify predictors for development of Pneumocystis jirovecii pneumonia (PJP) in kidney and simultaneous kidney and pancreas transplant recipients in the present era of universal primary prophylaxis.MethodsWe reviewed adult recipients of kidney transplant or simultaneous pancreas and kidney transplant at the University of Wisconsin between January 1, 1994 and December 31, 2016. Patients diagnosed with PJP during this time frame were included. Controls were randomly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…In recipients of kidney and/or kidney/pancreas transplants, cytomegalovirus (CMV) viremia (median viral load 3685 IU/ ml) was a risk factor for PCP, with 90% of patients having CMV 1 year prior to PCP and 89% had active CMV infection when diagnosed with PCP [26]. The association with CMV was not seen in HSCT patients, where lymphopenia, acute graft-versus-host disease and the use of immunosuppressive agents were significantly associated with PCP post-allogeneic HSCT [5].…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…In recipients of kidney and/or kidney/pancreas transplants, cytomegalovirus (CMV) viremia (median viral load 3685 IU/ ml) was a risk factor for PCP, with 90% of patients having CMV 1 year prior to PCP and 89% had active CMV infection when diagnosed with PCP [26]. The association with CMV was not seen in HSCT patients, where lymphopenia, acute graft-versus-host disease and the use of immunosuppressive agents were significantly associated with PCP post-allogeneic HSCT [5].…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…6 Immunosuppressant agents, CMV infection, allograft rejection, and a low lymphocyte count have been proposed as risk factors for PCP in KTRs after post-transplantation prophylaxis. 3,5,7 In a meta-analysis of 15 studies, allograft rejection and CMV infection were identified as risk factors for PCP development. The study further suggested that extended prophylaxis targeting allograft rejection and CMV infection may reduce the risk of PCP.…”
Section: Introductionmentioning
confidence: 99%
“…Median time from transplant to CMV infection was 2.2 months (IQR 1.7-3.6), time from transplant to rejection 5.0 months (IQR 0.6-25.0). Time to PCP development after rejection (median [IQR], 6[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] months) was slightly shorter than after CMV infection (median [IQR], 9[5][6][7][8][9][10][11][12]), although this difference was not statistically significant (P = .18) (Table 3,…”
mentioning
confidence: 99%
“…Indeed, we found patients who experienced CMV infection preceded by acute rejection had a twofold increased risk of graft loss and mortality compared to those with CMV without precedent rejection. CMV is an immunomodulating virus that has been associated with increased incidence of other concomitant infections, and subsequent increased mortality . Indeed, this has been described in the setting of rejection treatment .…”
Section: Discussionmentioning
confidence: 99%